ĐẶC ĐIỂM CÁC THÀNH TẠO MAFIC - SIÊU MAFIC KHU VỰC NAM HÀ GIANG VÀ BẮC PHỐ RÀNG - Niên, Bùi Ấn; Hòa, Trần Trọng; Phượng, Ngô Thị; Thành, Hoàng Hữu; Anh, Trần Tuấn; Dung, Phạm Thị (Vietnam Journal of Earth Sciences, 2017)
The new quantitative analysis of mafic and ultramafic formations situated in South Song Chay uplift had been carried out recently. The results show that the rocks have high magnesium, low titannium (0,02-0,04 wt.%), aluminum (1,31-2,4wt.%) and very low alkaline (0,03-0,09 wt.%). Orthopyroxeneis magnesia-enstatite and clinopyroxene isaugite low calcium. Olivine is forsterite {F0=90-93%)and very low GaO content (<0,04 wt.%).The above mentioned features reveal the deepand depleted mantle drivered source of these formations.Their geochemical partern is similar to MORBand can be compared with the Song Ma ophiolite of Northwest Vietnam and the Shuanggou, Luabusa, Babu ophiolite in Southwest China.Nevertheless, these are only initial data. Inorder to understand the nature of this ophiolite belt, future investigation should be worked on the gabbro, diabase and plagiogranite ... of the Bach Sa complex and cherts, basalts and greenshist ... of the Ha Giang Formation as well.